Cybersecurity program development for business : the essential planning guide - Moschovitis, Christos J. P. (Hoboken : Wiley, 2018)
"Get answers to all your cybersecurity questions In 2016, we reached a tipping pointa moment where the global and local implications of cybersecurity became undeniable. Despite the seriousness of the topic, the term "cybersecurity" still exasperates many people. They feel terrorized and overwhelmed. The majority of business people have very little understanding of cybersecurity, how to manage it, and what's really at risk. This essential guide, with its dozens of examples and case studies, breaks down every element of the development and management of a cybersecurity program for the executive. From understanding the need, to core risk management principles, to threats, tools, roles and responsibilities, this book walks the reader through each step of developing and implementing a cybersecurity program. Read cover-to-cover, its a thorough overview, but it can also function as a useful reference book as individual questions and difficulties arise. Unlike other cybersecurity books, the text is not bogged down with industry jargon Speaks specifically to the executive who is not familiar with the development or implementation of cybersecurity programs Shows you how to make pragmatic, rational, and informed decisions for your organization Written by a top-flight technologist with decades of experience and a track record of success If youre a business manager or executive who needs to make sense of cybersecurity, this book demystifies it for you."--
"This essential guide, with its dozens of examples and case studies, breaks down every element of the development and management of a cybersecurity program for the executive. From understanding the need, to core risk management principles, to threats, tools, roles and responsibilities, this book walks the reader through each step of developing and implementing a cybersecurity program. Read cover-to-cover, it's a thorough overview, but it can also function as a useful reference book as individual questions and difficulties arise"--
What's in It for Me?; Attitude Adjustment!; The Right Message, Delivered the Right Way; Cybersecurity-Awareness Training; CHAPTER 13: Living Cybersecure!; General Data Protection Regulation (GDPR), Privacy, and Regulators; Artificial Intelligence and Machine Learning; Blockchain; Quantum Computing; BIBLIOGRAPHY; APPENDIX: Clear and Present Danger; INDEX; END USER LICENSE AGREEMENT.
Includes bibliographical references and index.
Machine generated contents note: Preface Acknowledgments About the Author Chapter 1 Understanding Risk Chapter 2 Everything You Always Wanted to Know About Tech (But Were Afraid to Ask Your Kids) Chapter 3 A Cybersecurity Primer Chapter 4 Management, Governance, and Alignment Chapter 5 Your Cyber Security Program: A High-Level Overview Chapter 6 Assets Chapter 7 Threats Chapter 8 Vulnerabilities Chapter 9 Environments Chapter 10 Controls Chapter 11 Incident Response Planning Chapter 12 People Chapter 13 Living Cybersecure! Bibliography.
Print version record and CIP data provided by publisher.
John Wiley and Sons
Keywords: Information technology -- Management; Business enterprises -- Computer programs; Computer networks -- Security measures; Computer industry; Technologie de l'information -- Gestion; Entreprises -- Logiciels; x -- Mesures; Informatique -- Industrie; BUSINESS & ECONOMICS -- Industries -- Computer Industry; Computer industry; Computer networks -- Security measures; Information technology -- Management